UPAYA PENINGKATAN KEMAMPUAN APARATUR TERHADAP PELAKSANAAN TUGAS ADMINISTRASI PEMERINTAH DI KANTOR DESA BILA RIASE KECAMATAN PITU RIASE KABUPATEN SIDENRENG RAPPANG - Sulviah Sulviah; Kamaruddin Sellang; Andi Uceng (JIA: Jurnal Ilmiah Administrasi, 2022)
This study aims to determine the Efforts to Improve the Capability of the Apparatus for the Implementation of Government Administrative Duties at the Bila Riase Village Office, Pitu Riase District, Sidenreng Rappang Regency and to determine the factors that influence the Apparatus Capacity Building on the Implementation of Government Administrative Duties at the Bila Riase Village Office, Pitu Riase District, Sidenreng Rappang Regency. . The population in this study was the number of family cards at the Bila Riase Village Office, Pitu Riase District, amounting to 850 families. The number of samples was taken by means of a total random sample using Yount's formula so that the number of respondents who will be used as respondents is 42 people. Data collection techniques used are observation, interviews, questionnaires and literature study. The collected data is then used quantitative analysis techniques with frequency tables. The results showed that the Efforts to Improve the Capability of the Apparatus for the Implementation of Government Administration Duties at the Bila Riase Village Office, Pitu Riase District, Sidenreng Rappang Regency were categorized as good with a score of 62.51%. The highest indicator is the Cospetual Ability. Factors that affect the capacity building of the apparatus towards the implementation of government administrative tasks at the Bila Riase Village Office, Pitu Riase District, Sidenreng Rappang Regency, namely the Knowledge Factor marked by the understanding of the Bila Riase Village apparatus about appropriate services, categorized as good with a score of 64.2%. The Skills factor is marked by the ability of the Bila Riase Village apparatus to effectively complete the work, which is categorized as good with a score of 66.6%.